Chickens productivity selection affects immune system genes - А. М. Borodin; Ya. I. Alekseev; K. E. Gerasimov; N. V. Konovalova; E. V. Тerentjeva; D. N. Efimov; Zh. V. Emanuilova; L. I. Tuchemskiy; A. A. Komarov; V. I. Fisinin (Вавиловский журнал генетики и селекции, 2020)
The quantitative trait loci associated with the immune properties of chickens are of interest from the point of view of obtaining animals resistant to infectious agents using marker-assisted selection. In the process of selecting markers for genomic selection in broiler-type chickens, a non-standard genotype frequency of the RACK1 gene allele (SNP Gga_rs15788101) in the B5 line of broiler-type chicken cross Smena 8 was identified and it was suggested that this gene was involved in selection. Therefore, it was decided to investigate the available polymorphisms in the three genes responsible for the IgY titer (DMA, RACK1 and CD1B). Molecular typing of single nucleotide polymorphisms of three loci revealed an approach to fixation of the unfavorable allele of the DMA gene (SNP Gga_rs15788237), an approach to fixation of the unfavorable allele of the RACK1 gene and the prevalence of the favorable CD1B gene allele (SNP Gga_rs16057130). Analysis of the haplotypes revealed a strong linkage disequilibrium of these genes. This suggests that these genes experience selection pressure. Analysis of the protein-coding sequences of the CD1B and DMA genes of various breeds of chickens revealed a negative selection of these genes. In order to understand whether the fixation of the studied alleles is the result of artificial selection of the B5 line of the cross Smena 8, an analysis of similar loci in layer chickens Hisex White was carried out. The frequencies of the alleles at the loci of the CD1B gene (Gga_rs16057130) and the RACK1 gene (Gga_rs15788101) in the Hisex White chicken genome differ from the frequencies of the alleles obtained for chickens of the B5 line of the cross Smena 8. It can be assumed that the fixation of the allele in the DMA gene (SNP Gga_rs15723) is associated with artificial or natural selection, consistent in broilers and layers. Changes in the loci Gga_rs16057130 and Gga_rs15788101 in the B5 line of the Smena 8 chickens are most likely associated with artificial selection of broiler productivity traits, which can subsequently lead to fixation of alleles at these loci. Artificial breeding of chickens leads to degradation of the variability of genes encoding elements of the immune system, which can cause a decrease in resistance to various diseases. The study of the negative impact of selection of economic traits on immunity should provide means to mitigate negative consequences and help find ways to obtain disease-resistant animals.